Role of Droplets and Aerosols in Transmission of COVID-19 in Dental Practice: A Literature Review - S Helli; E Shafiee; K Mogharrab Alile (Islamic Azad University, 2022)
Background and Aim: This study sought to review the role of aerosols and droplets in transmission of coronavirus disease 2019 (COVID-19) in dental practice .   Materials and Methods: Published papers concerning the transmission routes of COVID-19 in dental environment were retrieved from the search engines, websites of related health organizations, and electronic databases. Out of primarily retrieved 120 articles, 40 articles met the inclusion criteria. Results: Many Studies reported that the main transmission routes of COVID-19 were direct contact, droplets and aerosols. Because of the adjacency to the patient's oral cavity and use of aerosol-generating headpieces, dental practitioners are at high risk of COVID-19. Adherence to clinical protocols and guidelines in the working environment was highly emphasized in all studies to minimize the risk of infection and prevent cross-contamination in dental office setting. Conclusion: Dental healthcare providers should be well aware of the most recent guidelines and protocols to prevent COVID-19 transmission and constantly update their knowledge in this regard.